An overview of the clinical use of cabozantinib in the treatment of advanced non-clear-cell renal cell carcinoma (NCCRCC). (May 2020) - D'Angelo, Alberto; Bagby, Stefan; Di Pierro, Giulia; Chirra, Martina; Nobili, Stefania; Mini, Enrico; Villari, Donata; Roviello, Giandomenico
Graphical abstract: Abstract: Patients diagnosed with non-clear renal cell carcinoma have often been excluded from clinical trials due to the shortage of treatments available, the low incidence of tumours with non-clear histology, and the corresponding diversity of intrinsic molecular features. This approach led to a knowledge gap in finding the optimal treatment for patients diagnosed with non-clear cell renal carcinoma. Cabozantinib, a potent multiple tyrosine kinase receptor inhibitor, has been recently investigated in patients with non-clear cell histologies of renal cell cancer. In this review, we have summarized available data on the use of cabozantinib in non-clear renal cell carcinoma.